WHAT IS THE AXIS OF EVIL? - Romanyuk, Oleksandr (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
This article is devoted to the emergence and transformation of the concept of the «Axis of Evil», which is relatively new in political science and the theory of international relations. There are two stages of its interpretation, in the first of which the Axis of Evil was understood as the political regimes of countries that sponsor international terrorism and develop biological, chemical, and nuclear weapons, in the second – autocracies that began to fan the flames of a new world war with their actions. It is emphasized that the transition from the first stage to the second was caused by Russia's full-scale military aggression against Ukraine, which caused a crisis in the world order.The author believes that the main actors of the Axis of Evil should primarily include Russia, which started the largest military conflict in Europe since the Cold War, as well as those countries that directly help it achieve its aggressive goals. He includes North Korea and Iran among these. These countries supply Russia with a critical mass of weapons, without which it would not have been able to withstand this war for four years, and North Korea has even sent its military contingent to Russia. This alliance is united by a common goal – to oppose the spread of the ideological, political, and economic influence of Western democracies in the world. However, each of its countries has its own geopolitical goals, which may conflict with those of other participants. The problem of communist China occupies a special position in terms of belonging to the Axis of Evil. On the one hand, the PRC officially declares its commitment to preserving peace, its willingness to adhere to the principles of world order, and openly does not assist other members of this alliance in committing aggression. On the other hand, it economically, technologically, and politically supports aggressor countries. According to the author, China, in the context of the development of the situation in the modern world, is similar to a director who, being behind the scenes, determines for the actors how to play their roles on stage. The conclusions emphasize that the actions of these states threaten humanity with a new world war. To prevent it, civilized countries, whose combined potential significantly exceeds the combined potential of aggressive autocracies, must join forces to curb the aggressors. Unfortunately, after Donald Trump came to power in the United States, the creation of an alliance to effectively counter the Axis of Evil has become a big problem.